The Integrated Model For Quality Improvement For Semiconductor Companies - Abd Suki, Nur Syazwani (2017)
High quality product helps to maintain customer satisfaction and reduces the risk and cost of replacing faulty goods. One of the factors that affect quality performance is the defects of the products, which lead to lower productivity and profit. The application of quality improvement in semiconductor manufacturing company is important to ensure the quality of finished products as well as to fulfill customer’s requirement. The purpose of this research is to develop a model in seeking an improvement in quality process where DMAIC (Define-Measure-Analyze-Improve-Control) being the main approach with infusion of TRIZ (Theory of Inventive Problem Solving) technique. The DMAIC method is an integral part of Six Sigma initiatives and often being applied in quality improvement. DMAIC model provided structured methodology upon analyze process. Meanwhile, TRIZ technique applied strategies and tools to find out the best solutions to avoid numerous trials and errors during problem solving process. In this research, these two approaches are integrated in designing a new quality improvement model named as DMAIES (Define-Measure-Analyze-Improve-Evaluate-Sustain). The TRIZ technique is applied in the Improve phase, while the others selected quality tools and technique is adopted in the other phases of the DMAIES model. This model was verified through a case study in semiconductor company. The case study considered two different environments, namely the manufacturing and assembly processes. The outcome of the case study is reduction of major defect and improvement in the percentage of yield, hence improve the quality process.